Two new records of mealybugs (Coccomorpha: Pseudococcidae) on succulent plants (Crassulaceae) from Korea - Jinyeong Choi (Elsevier, 2021)
Phenacoccus solani Ferris, 1918 and Vryburgia distincta (De Lotto, 1964) are herein reported occurring on succulent plants (Echeveria spp.) in South Korea. Both species have not been documented from South Korea except for quarantine inspection reports. In this study, diagnoses, descriptions, and photographs of the two species are provided with general information about their host plants and distributions.